2008
DOI: 10.1080/00140130802277539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a desk attachment board on posture and muscle activity in women during computer work

Abstract: Working at a computer is part of a large number of jobs and has been associated with upper extremity musculoskeletal disorders and back pain. The study evaluated the effects of a board attachment on upper extremity and back. The findings are mixed in that the board may have a positive effect in preventing back pain, but may be detrimental to upper extremities. Effect of a desk attachment board on upper extremity and trunk posture, and muscle activity was assessed in women video display terminal users. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 29 publications
1
12
0
3
Order By: Relevance
“…Also, training exercises during frequent work breaks play an essential role to improve the hazardous health outcome of exposure to ergonomic hazards at work for those dealing with VDT. These modifications are supported by the current literature on workspace ergonomics (20,21,22) . A randomized controlled clinical intervention study, carried out in Spain, revealed that episodes of musculoskeletal disorder-related temporary work disability were shorter in the intervention group than in the control group.…”
Section: Introductionsupporting
confidence: 67%
“…Also, training exercises during frequent work breaks play an essential role to improve the hazardous health outcome of exposure to ergonomic hazards at work for those dealing with VDT. These modifications are supported by the current literature on workspace ergonomics (20,21,22) . A randomized controlled clinical intervention study, carried out in Spain, revealed that episodes of musculoskeletal disorder-related temporary work disability were shorter in the intervention group than in the control group.…”
Section: Introductionsupporting
confidence: 67%
“…One example found in a study by Dumas et al [14] that looked at the effect of a desk attachment board on back and upper extremity muscle activity and posture. The participants included healthy women and found that the board may prevent back pain while possibly increasing upper extremity pain.…”
Section: Implications For Specific Interventionsmentioning
confidence: 99%
“…15 There are few studies that have looked at the musculoskeletal syndrome in a whole picture, which considered forearm, shoulder, neck and back muscles, and posture together. 16 Based on cumulated evidence, we performed the meta-analysis on 4 studies with 323 cases and 332 controls. To our knowledge, this is the first meta-analysis conducted with respect to the association between the forearm support and upper body syndrome.…”
Section: Commentmentioning
confidence: 99%